Promoting Inclusive Education: Strategies for Addressing Diversity and Equity in the Classroom - Andika Dirsa (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the concepts, challenges, opportunities and adaptation strategies of inclusive education in various cultural and social contexts. Using a systematic literature review method, this research analyzes various scientific articles published in recent years related to inclusive education. Research findings reveal that inclusive education is a dynamic concept with the aim of providing equal educational opportunities for all individuals, but challenges in its implementation still exist. Nonetheless, there are opportunities that can be exploited to promote inclusive education in various cultural and social contexts, such as increased global awareness and advances in educational technology. This study provides important implications for the development of more effective inclusive education policies and practices in the future.